The effects of catecholamine depletion on the neural response to fearful faces in remitted depression. (14th April 2014) - Homan, Philipp; Drevets, Wayne C.; Hasler, Gregor
Abstract: Recent evidence suggests that increased psychophysiological response to negatively valenced emotional stimuli found in major depressive disorder (MDD) may be associated with reduced catecholaminergic neurotransmission. Fourteen unmedicated, remitted subjects with MDD (RMDD) and 13 healthy control subjects underwent catecholamine depletion with oral α -methyl- para -tyrosine (AMPT) in a randomized, placebo-controlled, double-blind crossover trial. Subjects were exposed to fearful (FF) and neutral faces (NF) during a scan with [ 15 O]H2 O positron emission tomography to assess the brain–catecholamine interaction in brain regions previously associated with emotional face processing. Treatment with AMPT resulted in significantly increased, normalized cerebral blood flow (CBF) in the left inferior temporal gyrus (ITG) and significantly decreased CBF in the right cerebellum across conditions and groups. In RMDD, flow in the left posterior cingulate cortex (PCC) increased significantly in the FF compared to the NF condition after AMPT, but remained unchanged after placebo, whereas healthy controls showed a significant increase under placebo and a significant decrease under AMPT in this brain region. In the left dorsolateral prefrontal cortex (DLPFC), flow decreased significantly in the FF compared to the NF condition under AMPT, and increased significantly under placebo in RMDD, whereas healthy controls showed no significant differences. Differences between AMPT and placebo of within-session changes in worry-symptoms were positively correlated with the corresponding changes in CBF in the right subgenual prefrontal cortex in RMDD. In conclusion, this study provided evidence for a catecholamine-related modulation of the neural responses to FF expressions in the left PCC and the left DLPFC in subjects with RMDD that might constitute a persistent, trait-like abnormality in MDD.